Analysis processes independent generator with contactless cascade three-phase modulated by exciter circuit in one star and combined connection modulator phase during work unit induction motor - Vasyliv, K. (Енергетика і автоматика, 2015)
The method of mathematical experiment performed studies of electromagnetic and electromechanical processes that occur in autonomous power supply system on the basis of asynchronized generator with three phase modulated energizer. The analysis of processes in terms robotoprydatnosti supply system during its work on the unit induction motors. Established regularities of electromagnetic and elektromehanichnyh processes depending on the parameters of the control switch.